TWO METAMORPHIC STAGES IN THE SVECOFENNIAN DOMAIN: EVIDENCE FROM THE ISOTOPIC GEOCHRONOLOGICAL STUDY OF THE LADOGA AND SULKAVA METAMORPHIC COMPLEXES - Baltybaev Sh.K.; Levchenkov O.A.; Levsky L.K.; Eklund O.; Kilpeläinen T. (My University, 2006)
The Ladoga, Russia, and adjacent Sulkava, southeastern Finland, metamorphic complexes are the two largest "granulite" provinces of the Svecofennian domain. In this area, the domain is composed of outer and inner zones. Sulkava is situated in the inner zone, which principally can be compared to the accretionary arc complex of Southern Finland. Ladoga is situated in the outer zone, which is correlated with the accretionary arc complexes of central and Western Finland. The complexes contain different metamorphic assemblages, which are caused by the different composition of the sedimentary protoliths: the rocks of the Sulkava metamorphic complex are higher in Al and K than those of the Ladoga Complex. Pb-Pb step leaching dating was used to determine the age of prograde sillimanite from both complexes. The dates thus obtained constrain metamorphic peaks for the Sulkava and Ladoga complexes at 1799 ± 19 Ma and 1878 ± 7 Ma, respectively, which is consistent with the U-Pb monazite ages of gneisses from both of the complexes. The differences in the ages of the metamorphic minerals from these complexes reflect the Early Svecofennian (1.89-1.86 Ga) and Late Svecofennian (1.83-1.79 Ga) metamorphic stages in the Fennoscandian Svecofennides. © 2006 Nauka/Interperiodica.